Investigation on parametrically excited motions of point absorbers in regular waves. (1st January 2016) - Tarrant, Kevin; Meskell, Craig
Abstract: Free floating objects such as a self-reacting wave energy converter (WEC) may experience a condition known as parametric resonance. In this situation, at least two degrees of freedom become coupled when the incident wave has a frequency approximately twice the pitch or roll natural frequency. This can result in very large amplitude motion in pitch and/or roll. While classic linear theory has proven sufficient for describing small motions due to small amplitude waves, a point absorber WEC is often designed to operate in resonant conditions, and therefore, exhibits significant nonlinear responses. In this paper, a time-domain nonlinear numerical model is presented for describing the dynamic stability of point absorbers. The pressure of the incident wave is integrated over the instantaneous wetted surface to obtain the nonlinear Froude–Krylov excitation force and the nonlinear hydrostatic restoring forces, while first order diffraction-radiation forces are computed by a linear potential flow formulation. A numerical benchmark study for the simulation of parametric resonance of a specific WEC—the Wavebob—has been implemented and validated against experimental results. The implemented model has shown good accuracy in reproducing both the onset and steady state response of parametric resonance. Limits of stability were numerically computed showing the instability regions in the roll and pitch modes. Abstract : Highlights: Simulation of parametric roll in a two-body heaving wave energy converter. Numerical scheme includes nonlinear Froude–Krylov and nonlinear restoring forces. Simulation validated with 17th scale wave tank data. Heave, roll and pitch modes strongly coupled under parametric resonance conditions. Stability limit for the WEC resemble that of the first Mathieu instability zone.